Wideband matching circuit for mmWave series fed patch array antenna - Mohan, Manoj Prabhakar (2023)
A novel wide band matching circuit for the series fed patch array antenna at 80 GHz is proposed in this paper. The series fed patch array is designed with amplitude tapered configuration. First, the series fed patch array is matched using stub loaded transmission line (TL) with narrow band. Later, it is converted to wide band matching circuit using three quarter wave transformers and two half wavelength stubs. The sizes of these half wavelength stubs are reduced using the stub loaded and step impedance TLs. The simulated results of the series fed patch array with and without the connector are presented. The simulated -10 dB reflection coefficient bandwidth with connector is from 77.125 GHz to 83.95 GHz and the simulated co-polarized gain with connector is 13.73 dBi. The designed antenna array is fabricated along with the matching circuit and tested experimentally. The measured -10 dB reflection coefficient bandwidth is from 76.73 GHz to 86.08 GHz with the measured gain of the antenna is 13.3 dBi at 81.44 GHz.